PATH-13. CHARACTERIZING TEMPORAL GENOMIC HETEROGENEITY IN PEDIATRIC LOW-GRADE GLIOMAS. (9th November 2020) - Lazow, Margot; Schafer, Austin; Hoffman, Lindsey; Osorio, Diana; Boué, Daniel; Rush, Sarah; Wright, Erin; Lane, Adam; DeWire, Mariko; Smolarek, Teresa; Sipple, Jared; Taggert, Heather; et al.
Abstract: BACKGROUND: Recent discoveries have provided valuable insight into the genomic landscape of pediatric low-grade gliomas (LGGs) at diagnosis, facilitating molecularly targeted treatment. However, little is known about their temporal and therapy-related genomic heterogeneity. An adequate understanding of the evolution of pediatric LGGs' genomic profiles over time is critically important in guiding decisions about targeted therapeutics and diagnostic biopsy at recurrence. METHODS: Fluorescence in situ hybridization, mutation-specific immunohistochemistry, exome analyses, and/or targeted sequencing were performed on paired tumor samples from diagnostic and subsequent surgeries. RESULTS: Ninety-four tumor samples from 45 patients (41 with two specimens, four with three specimens) from three institutions underwent testing. Conservation of BRAF fusion, BRAF V600E mutation, and FGFR1 rearrangement status was observed in 100%, 98%, and 96% of paired specimens, respectively. No loss or gain of IDH1 mutations or NTRK2, MYB, or MYBL1 rearrangements were detected over time. Histologic diagnosis remained the same in all tumors, with no acquired H3K27M mutations or malignant transformation. Changes in CDKN2A deletion status occurred in 10 patients (40%), with acquisition of CDKN2A deletion in seven (including three who received chemotherapy [two with temozolomide] and one who received radiation) and loss in three (including one who received targeted therapy and radiation). A trend toward shorter time to progression was observed among patients with acquired CDKN2A deletions compared to patients without acquisition of this alteration (median: 5.5 versus 14.0 months [p=0.078]). CONCLUSIONS: Most targetable genetic aberrations in pediatric LGGs, including BRAF alterations, are conserved at recurrence and following chemotherapy or radiation. However, changes in CDKN2A deletion status over time were demonstrated. Acquisition of CDKN2A deletion may define a higher risk subgroup of pediatric LGGs with a poorer prognosis. Given the potential for targeted therapies for tumors harboring CDKN2A deletions, biopsy at recurrence may be indicated in certain patients, especially those with rapid progression.